2012
DOI: 10.1038/modpathol.2011.196
|View full text |Cite
|
Sign up to set email alerts
|

Mixed versus pure variants of desmoplastic melanoma: a genetic and immunohistochemical appraisal

Abstract: Desmoplastic melanoma is subclassified into pure and mixed variants with a higher rate of lymph node metastasis in the latter. Given that reasons for these biological differences are not currently known, we investigated these subtypes with techniques that included genetic and immunohistochemical analyses of 43 cases of desmoplastic melanoma (24 pure, 19 mixed). Direct DNA sequencing was performed on BRAFV600E, RET gene (coding region on exon 11) and KIT (exons 11, 13 and 17). Immunohistochemical stains were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
3
45
0
1
Order By: Relevance
“…[1][2][3] The BRAFV600E mutation is seen at particularly high rates in primary and metastatic melanoma (20-70%), papillary thyroid carcinoma (40-70%), colorectal carcinoma (5-10%), and in select benign tumors such as melanocytic nevi. 2,[4][5][6][7][8][9][10] Given its prevalence and role in increasing tumor cell proliferation and metastases, BRAFV600E has emerged as an important biomarker for clinicians. In early melanomas, the BRAF mutation status has not been shown to affect overall survival; however, in metastatic melanoma, it has been associated with a poorer survival rate.…”
mentioning
confidence: 99%
“…[1][2][3] The BRAFV600E mutation is seen at particularly high rates in primary and metastatic melanoma (20-70%), papillary thyroid carcinoma (40-70%), colorectal carcinoma (5-10%), and in select benign tumors such as melanocytic nevi. 2,[4][5][6][7][8][9][10] Given its prevalence and role in increasing tumor cell proliferation and metastases, BRAFV600E has emerged as an important biomarker for clinicians. In early melanomas, the BRAF mutation status has not been shown to affect overall survival; however, in metastatic melanoma, it has been associated with a poorer survival rate.…”
mentioning
confidence: 99%
“…Regarding desmoplastic malignant melanoma a complete absence of BRAF mutations 21 as well as a reduced mutation rate 22 has been reported. Recently, Miller et al 23 have observed a lack of BRAF mutations in pure desmoplastic malignant melanoma compared to a low frequency in the mixed subtype and a trend toward an increased RETp frequency in pure desmoplastic malignant melanoma. Kim et al 24 extended mutation analysis in desmoplastic malignant melanoma to BRAF and KIT reporting wild-type BRAF and KIT in all tumors investigated.…”
Section: Discussionmentioning
confidence: 99%
“…22 Subclassification of desmoplastic malignant melanoma into pure and mixed type is not only clinically relevant, but also apparently reflects different mutation patterns as well. Miller et al 23 have recently shown that pure desmoplastic malignant melanoma is devoid of BRAF mutations as opposed to mixed desmoplastic malignant melanoma, which did exhibit BRAF mutations albeit at a low level (6% of cases). In addition, absence of BRAF mutations in an investigation including 10 desmoplastic melanomas (not further subclassified) has been reported by another group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The examples of desmoplastic melanomas, including both mixed and pure types, were based on established morphologic criteria. 9 All cases of synovial sarcomas harbored the SYT-SSX t(X;18) chromosomal translocation, and all cases of clear-cell sarcomas harbored the EWS break apart by fluorescent in situ hybridization (FISH).…”
Section: Case Selectionmentioning
confidence: 99%